Growth of market gardening for local sales in the Mount Everest tourist region of Pharak, Nepal - Abadia Céline; Aubriot Olivia; Smadja Joëlle; Vaillant Michel; Oswald Marc (Revue de Géographie Alpine)
Pharak region, traversed by the Everest trekking route, sees thousands of hikers come through each year to discover the Khumbu high-mountain landscapes. Formerly a region devoted to livestock farming, Pharak has experienced significant socio-economic changes since the early 1970s. The predominantly Sherpa population is gradually abandoning agro-pastoral activities in favour of greater participation in the tourism industry. By generating economic benefits, creating demand and capturing part of the labour force, tourism is engendering important transformations in the region’s agriculture. Trade is on the increase and market opportunities are reconfiguring the agrarian landscape. Market gardening, in particular, is gaining momentum and has become a new local business. This article highlights the originality of this mode of farming, which has developed in tandem with the growth of tourism but independently of the growth of cities and the construction of roads.